High-temperature stability of nitrate/nitrite molten salt mixtures under different atmospheres. (15th September 2018) - Villada, Carolina; Bonk, Alexander; Bauer, Thomas; Bolívar, Francisco
Highlights: New methodology was proposed to evaluate the thermal stability of molten salts. Long-term thermal stability was determined for molten nitrate/nitrite mixtures. The effect of nitrogen-oxygen atmospheres on nitrate molten salts was studied. Solar Salt and lithium mixtures are stable under both, nitrogen-oxygen atmosphere. Hitec molten salt is stable only under nitrogen atmosphere. Abstract: Molten salts are widely used as thermal energy storage media in the Concentrating Solar Power (CSP) technologies. The melting point and the thermal stability of the salt determine the applicable temperature range of the storage system. The focus of this paper is to evaluate the effect of different gas atmospheres on the thermal stability of binary Solar Salt and two ternary salt mixtures containing lithium nitrate (Lithium mixture) and sodium nitrite (Hitec). The isothermal stability experiments were carried out at 550 °C during 500 h and the results show that the initial decomposition reaction of nitrate to nitrite depends strongly on the gas atmosphere. It is observed that changes in the nitrate-nitrite-ratio are the key parameters influencing the melting temperatures of the salt mixtures. For example, for experiments with oxygen in the atmosphere a large increase of the liquidus temperature of the Hitec mixture was observed. Metal oxides are formed during the irreversible decomposition of nitrite-ions but are found to affect the solidus and liquidus temperature of the salt mixtures only marginally. No carbonate formation was detected according to titration analysis of the salt mixtures in our experiments due to the absence of carbon dioxide in the atmosphere.